Comparative Study between Drill Skill and Concept Attainment Model towards Physics Learning Achievement - Izaak Hendrik Wenno; Pieter Wattimena; Luky Maspaitela (Institute of Advanced Engineering and Science, 2016)
Alternative learning model that can be used in teaching physics to overcome the problems of lack of student learning achievement is a model of skill training (drill skills, and the concept attainment model. Drill skill model is a teaching technique in which students carry out training activities on what they have learned, so that the material already taught more embedded in the minds of students, and students will have the dexterity or higher, while the concept attainment is a model of achievement of learning model that is designed to help students to be more easily learn a concept. The purpose of this study was to compare the results between student who was teached with drill skill model and concept attainment model. The quasi-experimental type was used. Sampling was done randomly in order to obtain two classes one for the first experimental group with drill skill, and the second one for the second experimental group with concept attainment model. These results suggest that the science-physics learning achievement of students with drill skill model is better than using a concept attainment model.